Wage flexibility in a unionized economy with stable wage dispersion - Carlsson, Mikael; Häkkinen Skans, Iida (Bonn, 2019)
"The paper estimates how wages respond to changes in regional unemployment using detailed Swedish micro data. The study is set in an economy with close to complete union coverage where real wages have grown continuously in all parts of the wage distribution for the past 15 years, and where the aggregate wage dispersion has remained constant for the same period. Our results show that this aggregate stability is coupled with non-trivial flexibility in terms of wage adjustments to changes in regional unemployment. Accounting for the fluctuations in composition of the employees is important for the estimated elasticity of wages. Wage adjustments are larger for employees with high unemployment risk and for new hires entering from unemployment."